Effect Of Strengthening And Proprioceptive Exercises On Balance And ADLs In Knee Osteoarthritis - Vaibhav Namdev; Huma Zahoor Ahmed Siddiqui; Monika Sharma (Revista Electronica de Veterinaria, 2024)
Degenerative knee arthritis could be a chronic joint disease, primarily occurring in aged men and ladiesKnee degenerative arthritis is characterized not solely by ache however it occursalong with weakness in muscles which cause restrictions in performing daily activities and helps to bear stresses which occur due to overload of work